Predictably irrational : the hidden forces that shape our decisions - Ariely, Dan (HarperCollins, 2009)
An evaluation of the sources of illogical decisions explores the reasons why irrational thought often overcomes level-headed practices, offering insight into the structural patterns that cause people to make the same mistakes repeatedly.